2019
DOI: 10.4067/s0717-95022019000200584
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir and Curcumin Directly Alters BAX/BCL2 and VEGF165b mRNA Levels to Suppress Human Squamous Cervical Carcinoma Cell Growth

Abstract: directly alters BAX/BCL2 and VEGF165b mRNA levels to suppress human squamous cervical carcinoma cell growth. Int. J. Morphol., 37(2):584-591, 2019. SUMMARY: Following the success of the highly active antiretroviral therapy, the potential of multidrug combination regimen for the management of cancer is intensely researched. The anticancer effects of curcumin on some human cell lines have been documented. Lopinavir is a FDA approved protease inhibitor with known apoptotic activities. Dysregulated apoptosis is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
2
0
1
Order By: Relevance
“…Due to the multitude of properties manifested by curcumin analogs, the diversity of applications of the natural compound will be further developed (Figure 2) as many as the issues related to the extraction, solubility, and stability of the parent compound will be solved. Due to its antioxidant and anti-inflammatory properties, modern applications of curcumin in the medical field targeting the treatment of neurodegenerative diseases [173][174][175][176] and cancer [177][178][179][180][181][182][183][184] will be further developed. Furthermore, studies have shown that, as a result of the metabolism process, curcumin can undergo two types of transformation.…”
Section: Future Developments Of Curcumin-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the multitude of properties manifested by curcumin analogs, the diversity of applications of the natural compound will be further developed (Figure 2) as many as the issues related to the extraction, solubility, and stability of the parent compound will be solved. Due to its antioxidant and anti-inflammatory properties, modern applications of curcumin in the medical field targeting the treatment of neurodegenerative diseases [173][174][175][176] and cancer [177][178][179][180][181][182][183][184] will be further developed. Furthermore, studies have shown that, as a result of the metabolism process, curcumin can undergo two types of transformation.…”
Section: Future Developments Of Curcumin-based Materialsmentioning
confidence: 99%
“…In vivo studies have shown the hepato-protective and nephrological effect of curcumin administered before and during chemotherapy [178]. The second approach is the use of curcumin as an adjuvant with the effect of the chemosensitization of cancer cells resistant to chemotherapeutic agents, through mechanisms of inhibition of the expression of anti-apoptotic proteins or intracellular transcription factors [181]. Thus, the results of studies performed on patients with colorectal cancer refractory to standard chemotherapy established a daily oral dose of 3.6 g curcumin without adverse effects.…”
Section: Future Developments Of Curcumin-based Materialsmentioning
confidence: 99%
“…Sin embargo los reguladores apoptóticos que se encuentran en la familia BCL-2, son las responsables de modular el umbral de respuesta a una amplia variedad de estímulos apoptóticos implicados en varios tipos de carcinomas humanos 22,23 . En cambio el factor de crecimiento endotelial vascular VEGF y sus receptores VEGFR son indispensables en el proceso de regulación de la vascularización y angiogénesis 24,25 . La unión VEGF/VEGFR-2 activa las vías de señalización en la angiogénesis, siendo el VEGFR-2 el principal receptor de VEGF 26 .VEGFR-2 es el receptor de tirosina quinasa transmembrana que se correlaciona con la proliferación, división, motilidad, adhesión y angiogénesis celular, cuyo bloqueo inhibe la proliferación de células cancerosas 27 .…”
Section: Introductionunclassified